Qualitative and quantitative characterization of aluminium alloys after corrosion testing - Nakazato, R. Z. [UNESP]; Codaro, E. N. [UNESP]; Ribeiro, L. M.F. [UNESP]; Hein, L. R.O. [UNESP] (My University, 2001)
The 2024 and 7050 aluminium alloys used as aircraft components were subjected to laboratory corrosion tests in sodium chloride solution. Light-microscope examinations make it possible to characterise morphological aspects of the localised corrosion. Image analysis was used to determine both depth and width of pits over corroded surfaces. It has been concluded that the annealing could reduce the pit growth in both alloys, by means of grains recrystallization or recovery. The 2024 alloy also tends to present an exfoliation mechanism, mainly throughout non-recrystallized and recrystallized grain boundaries, increasing the width and sustaining the depth of pit cavities during exposition to saline atmosphere. SEM and EDS analysis reveal the morphology and elemental distribution of the corrosion products formed after immersion corrosion test. Some of these products were identified by X-ray diffraction analysis. For 2024, Al(OH)3, Mg(OH)2 and Cu2O were found. Al(OH)3 and Cu2O were also found in 7050 samples.